Konsep Karakter dalam Perspektif Muslim dan Barat - Ahmad Fuadin; Syihabuddin Syihabuddin (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
The human need to have good and positive personality qualities in everyday life. Good character is very important to achieve true success and happiness in life. This research was conducted with the aim of understanding the concept of character in more depth, finding the correlation between character and success and happiness in life, as well as developing strategies and techniques to improve good character. This article discusses the concept of character from Muslim and Western perspectives. The research method used is a qualitative method with a library science approach. The results of this research show that from a Muslim perspective, good character is character that is based on religious teachings and always tries to improve itself from time to time. The concept of character in Islam has a close relationship with the moral and ethical values ​​taught by the Islamic religion. Meanwhile, from a western perspective, the concept of character has a broader meaning and is not related to a particular religion. A good character in a western perspective is a character who has strong and positive personality qualities. Even though there are different views, the concept of character still has a very important role in human life to achieve true success and happiness. Therefore, understanding and developing good character needs to be carried out by individuals from these two perspectives, so that they are able to overcome challenges in life in a positive and constructive way.